Safety of Cranberry: Evaluation of Evidence of Kidney Stone Formation and Botanical Drug-Interactions - Madden, Emily; McLachlan, Caleb; Oketch-Rabah, Hellen; Calderón, Angela I. (Planta Medica, 2021)
Cranberry is a popular ingredient in dietary supplements in the U. S. and is commonly used for preventing urinary tract infections. Because of its popularity in dietary supplements, the U. S. Pharmacopeial Convention has developed quality standards for cranberry ingredients. The purpose of this review was to determine if there are safety issues that should preclude the admission of cranberry ingredients from the development of U. S. Pharmacopeial Convention quality standards. Based on the totality of the data, the U. S. Pharmacopeial Convention concluded that cranberry ingredients are not known to be associated with serious risks to human health when consumed properly in dietary supplements and therefore were admitted for standard development. Although published clinical and animal data indicated that cranberry is not associated with serious adverse effects, interactions with warfarin and kidney stone formation were identified as potential risks. Studies have reported contradictory data regarding the role of cranberry in kidney stone formation, with some reports suggesting cranberry is associated with a reduced risk of kidney stones. Interactions with warfarin were not associated with moderate intakes of cranberry juice (240 – 480 mL). Some reports suggested that the potential for warfarin interactions requires excessive intakes of cranberry juice (1 – 2 L/day) or cranberry extracts (3000 mg/day). Cases of warfarin interactions with cranberry have mostly involved patients with serious illnesses and/or individuals taking concomitant medications. Based on these findings, the U. S. Pharmacopeial Convention concluded that the use of cautionary labeling statements regarding interactions with warfarin or kidney stone formation is not necessary in the development of quality standards for cranberry ingredients.
Keywords: cranberry; dietary supplement interactions; kidney stone safety; warfarin; urinary tract infection; Ericaceae